GAMBARAN KADAR KREATININ SERUM PADA PENDERITA DIABETES MELLITUS TIPE 2 DI RUMAH SAKIT UMUM PUSAT SANGLAH DENPASAR - ida arjani (Meditory : The Journal of Medical Laboratory, 2017)
ABSTRACTBackground Diabetes mellitus (DM) is a metabolic disease which characterized by hyperglycemia due to abnormalities insulin secretions, insulin performance, or both of them. The condition of insulin resistance in DM type 2 causes chronic complications such as diabetic nephropathy. It has become the second leading cause of end-stage kidney disease, and one of the most common and demaging complication of diabetes. The level of creatinine in blood is one of the parameters used to assess renal function, as in the plasma concentration and excretion in the urine within 24 hours. Serum creatinine levels greater than the normal value suggests an impaired renal function. Objective The purpose of this study was to determine serum creatinine levels in patients with DM type 2 in Sanglah General Hospital Denpasar. Methods The method uses an analytical study with description, used accidental sampling methods, involving 30 patients with DM type 2. Blood samples were analyzed for creatinine levels and data are presented as table. The reslts  of this study showed that 60% samples had high levels of serum creatinine, 30% samples had normal levels serum creatinine, and 10% samples had low levels serum creatinine. From the result was concluded, most patients with DM type 2 in Sanglah Genaral Hospital have highly serum creatinine levels.                                                        Keywords: creatinine serum, DM type 2